PEMETAAN JASA EKOSISTEM PENYEDIA PANGAN DI PROVINSI BALI - Wiranatha, I Made Alit; Nuarsa, I Wayan; Sudarma, I Made (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2024)
Ecosystem services are the benefits that humans obtain from ecosystems. With the growing demand to implement sustainable development, the need for information on ecosystem services is increasing as a consideration in various policies and development planning. In response to this need, the method that is often used is the preparation of ecosystem services maps using an approach obtained from land cover data. Many people think this method works well and saves a lot of time and money, especially for studying places on a global, regional, or national level, where it's easy to get data on land cover. The point of this study is to look at how the results of the 2018 and 2022 food supply ecosystem services maps compare. These maps were made by experts who thought about how ecosystem services could be used in different types of land and ecoregions. The Analytical Hierarchy Process (AHP) with the pairwise comparison method is used to figure out how much ecosystem services are worth in relation to land cover and ecoregions. The island of Bali was used as a study area, and food supply was the type of ecosystem service that was looked at. Ecoregion data results for 2022 with the high class being more dominant and having an area of 385,339.19 ha or the equivalent of 66.67%. Land cover in 2018 produced a dominant high class with an area of 288,931.82 ha or the equivalent of 48.74%. The land cover results in 2022 are predominantly high class with an area of 289,039.25 ha or the equivalent of 50.01% of the total area of the island of Bali. The analysis results from the combination of ecoregion and land cover in 2022 are predominantly high class with an area of 182,039.65 ha or the equivalent of 31.49%. Several factors can explain the connection between ecosystem processes and the benefits they provide, which can get around or lessen the problems with using land cover data. Keywords: Ecosystem Services; Expert Judgement; Ecoregion; Land Use Based Proxy